Differential oxidation conditions of substituted cyclobutanols derived from terpenes - Caturelli Kuran, Juan Alberto (2014)
The use of different oxidants for homochiral cyclobutanols afforded dissimilar products depending on the agent used. Dess–Martin periodinane allowed us to obtain the homochiral cyclobutanones and sodium hypochlorite produced only one of the two possible regioisomeric γ-butyrolactones.